Le protesi di capitello radiale - Butera, M.; La Gattuta, A.; Siragusa, F.; Abruzzese, A.; Valenti, G.D.; Zini, S.; Colaiuda, F. (Lo Scalpello - Journal, 2019)
RADIAL HEAD PROSTHESISRadial head prosthesis has been developed to reduce potential complications resulting from radial head resectionsurgery. Principal indications are for not fixable fractures associated with lesions of the other stabilisers (coronoid,olecranon, LCM, LCL, interosseous membrane). Starting from the first models, these prostheses have undergoneconsiderable changes both as regards materials and as regards types. Although today prosthetic replacement of theradial capital is considered as a valid option in the treatment of comminuted fractures, it is evident, however, thateven this type of treatment may not be free from complications.